ANALISA FAKTOR – FAKTOR YANG MEMPENGARUHI TABUNGAN MASYARAKAT PADA BANK UMUM DENGAN PENDEKATAN MODEL ECM - Evi Lusiana Christinawati (Jurnal Ekonomi Pembangunan, 2013)
To the effect this Research is subject to be menganalisis factor that regard society savings on public bank by use of approaching ECM wields annual data begin year 1985 until years 2009 be utilized this ECM'S approaching with consideration that this model feels equal to word relationship among variable one is analyzed well that in the short term and also on a long term. In theory PDB, savings rate of interest zoom, inflation rate is influential factor to savingses. studi's result in the short term points out that PDB and rate of interest zoom, having for positive and signifikan to society savings, but negative ascendant inflation whereas in the long term PDB interest rate, positive influential inflation rate to society savings. simultan's ala all that variable gets to be utilized big see it gets what far-reaching to society savings, but partially variable memilki's one the most influence dominant is PDB.